Preparation method and application of nitrogen and phosphorus co-doped zero-valent iron composite material
By introducing phosphate and lattice nitrogen under high-energy ball milling conditions and modifying zero-valent iron, the problem of reduced activity caused by oxidation during application is solved, and efficient removal of hexavalent chromium is achieved, with a removal rate of about 51 times and broadening the scope of pH application.
Patent Information
- Application Number
- CN202411723565.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-07
AI Technical Summary
The existing zero-valent iron is easily oxidized during application, resulting in a dense iron oxide layer on the surface, reducing its reactivity to hexavalent chromium and making it difficult to efficiently remove hexavalent chromium pollution.
By using reduced iron powder and diammonium hydrogen phosphate as raw materials under high-energy ball milling conditions, the synchronous introduction of phosphate and lattice nitrogen is achieved, combined with phosphate to modify the zero-valent iron shell, adjust the internal lattice structure of the iron, improve the electron transfer rate, and realize adsorption reduction coupling.
The removal efficiency of hexavalent chromium is significantly improved, and the removal is basically completed within 60 minutes, and the removal rate is increased by about 51 times. At the same time, the pH application scope is broadened, and the stability and reusability of the material are improved.
Smart Images

Figure CN119565556A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material engineering and environmental engineering, and in particular relates to a preparation method and application of a nitrogen-phosphorus co-doped zero-valent iron composite material. Background Art
[0002] With the rapid development of industry, heavy metal pollution in surface and groundwater has become increasingly serious. Heavy metal pollution of water bodies has been reported in most countries around the world. Chromium is a common toxic metal in nature, mainly existing in two stable oxidation states: hexavalent chromium and trivalent chromium. Hexavalent chromium is a highly toxic mutagenic carcinogen with strong oxidizing properties, and its toxicity is more than 100 times that of trivalent chromium. Long-term exposure to toxic or carcinogenic heavy metal-contaminated water bodies will cause various diseases and even cancer, leading to death. For example, chromium poisoning can lead to renal failure, lung cancer, and skin cancer. So far, adsorption of hexavalent chromium and in-situ reduction of hexavalent chromium to trivalent chromium is considered to be the most appropriate method to alleviate hexavalent chromium pollution.
[0003] As a promising groundwater remediation material, zero-valent iron has received extensive attention and in-depth research at home and abroad. Due to its abundant sources, low price, and strong reducibility, it is widely used to degrade and remove organic and inorganic pollutants in the environment. However, there are many problems in the practical application of zero-valent iron. The surface of zero-valent iron is easily oxidized by water and oxygen, and a dense iron oxide layer is generated on the surface to form a unique core-shell structure, which hinders the outward transfer of electrons inside zero-valent iron, resulting in a decrease in its reactivity to target pollutants. In recent years, the use of heteroatoms (including S, N, P, etc.) to dope and modify iron-based materials has shown stronger adsorption capacity, better catalytic performance and reduction performance, etc., because it can affect the distribution of valence electrons outside the Fe nucleus.
[0004] Therefore, this patent uses reduced iron powder and diammonium hydrogen phosphate as raw materials to achieve the simultaneous introduction of phosphate and lattice nitrogen under high-energy ball milling conditions. While phosphate combines with the zero-valent iron shell to improve the adsorption capacity, the introduction of highly electronegative N heteroatoms adjusts the internal lattice structure of iron to increase the electron transfer rate, achieving adsorption-reduction coupling enhancement, and providing a new strategy for the synthesis of micron zero-valent iron with high activity to remove hexavalent chromium. Summary of the invention
[0005] The purpose of the present invention is to overcome the limitations of existing zero-valent iron modification and application, and to provide a preparation method and application of a nitrogen-phosphorus co-doped zero-valent iron composite material. The preparation method of the material is not only simple to operate and has low preparation cost, but also the prepared nitrogen-phosphorus co-doped zero-valent iron composite material has a high removal efficiency for a variety of heavy metal pollutants.
[0006] The technical solution adopted by the present invention is:
[0007] 1. A method for preparing a nitrogen-phosphorus co-doped zero-valent iron composite material
[0008] Reduced iron powder and diammonium hydrogen phosphate (DAP) are used as raw materials, and phosphorus and nitrogen are doped on the surface and inside of zero-valent iron through solid phase ball milling to obtain a nitrogen-phosphorus co-doped zero-valent iron composite material.
[0009] Specifically, the method of the present invention is carried out according to the following steps: reduced iron powder and diammonium hydrogen phosphate are mixed in a molar ratio of 1:0-0.07 and placed in a ball mill jar of a ball milling equipment, the ball mill jar is filled with grinding media, and the obtained powder is washed with deionized water after grinding and dried under vacuum freezing conditions to obtain the nitrogen-doped zero-valent iron composite material; the grinding media are zirconium oxide beads with a diameter of 1-20 mm.
[0010] The ball mill grinds 40 times at 800 r / min, each time for 30 minutes, and pauses for 30 seconds after each time. The total grinding time is 20 hours.
[0011] During the solid phase ball milling process, the molar ratio of the added reduced iron powder to diammonium hydrogen phosphate is 1:0-0.07, preferably 1:0.035.
[0012] Preferably, the ball milling equipment is a planetary ball mill, a vibrating ball mill or a sand mill.
[0013] The grinding medium is one or more of agate beads, iron beads, steel beads and zirconium oxide beads, with a diameter of 1-20 mm. Preferably, the grinding medium is zirconium oxide beads.
[0014] 2. The present invention also provides a nitrogen-phosphorus co-doped zero-valent iron composite material obtained by the above preparation method; the composite material has phosphate groups bound to its surface and lattice nitrogen effects inside.
[0015] 3. The present invention also provides the use of the nitrogen-phosphorus co-doped zero-valent iron composite material in the repair of water bodies containing heavy metal pollutants.
[0016] The application is specifically as follows: adding the nitrogen and phosphorus co-doped zero-valent iron composite material into the hexavalent chromium aqueous solution to be treated, adjusting the pH, and then placing the composite material in a shaking table at a constant temperature of 25° C. and a rotation speed of 150 rpm / min.
[0017] The concentration of the nitrogen and phosphorus co-doped zero-valent iron composite material is 0.5 g / L-3 g / L. Preferably, the amount of the nitrogen and phosphorus co-doped zero-valent iron composite material is 2 g / L.
[0018] The hexavalent chromium aqueous solution is simulated wastewater, and the concentration of hexavalent chromium in the simulated wastewater is 2-15 mg / L. Preferably, the concentration of hexavalent chromium in the hexavalent chromium-contaminated water to be repaired is 5-10 mg / L.
[0019] The pH of the hexavalent chromium aqueous solution to be treated is adjusted to 3 to 9. Preferably, the pH of the hexavalent chromium aqueous solution to be treated is adjusted to 3 to 5.
[0020] The entire removal process of the present invention mainly includes adsorption-reduction-coprecipitation, in which adsorption and reduction play a key role. Adsorption is a prerequisite for the subsequent reduction of hexavalent chromium. Phosphate combines with the zero-valent iron shell in a monodentate mononuclear form, thereby reducing the binding energy of hexavalent chromium to the iron shell layer, allowing more hexavalent chromium to be bound to the surface of the zero-valent iron; and nitrogen is doped into the zero-valent iron lattice to increase the Fe-Fe bond length, weaken the interaction of the Fe-Fe bond, reduce the band gap width, and accelerate the transfer of electrons from the iron core to the iron shell, thereby achieving complete reduction of the hexavalent chromium adsorbed to the surface in the previous stage.
[0021] The beneficial effects of the present invention are:
[0022] 1) Compared with unmodified zero-valent iron, the nitrogen-phosphorus co-doped zero-valent iron composite material synthesized by the present invention has a greatly improved removal effect on hexavalent chromium, and the removal is basically completed within 60 minutes, and the removal rate is increased by about 51 times.
[0023] 2) The method of the present invention is simple to prepare, and only simple ball milling is required to achieve the simultaneous doping of nitrogen and phosphorus to obtain a nitrogen-phosphorus co-doped zero-valent iron composite material; and no toxic or hazardous substances are used or produced during the preparation process, which is green and safe.
[0024] 3) The nitrogen-phosphorus co-doped zero-valent iron composite material synthesized by this method has broadened the applicable pH range in application. Compared with unmodified zero-valent iron, it can achieve better pollutant removal effect under acidic and weakly alkaline conditions.
[0025] 4) The preparation process of the method of the present invention is safe, highly operable, and has a short reaction time. The method can use a conventional ball mill and conduct degradation experiments under aerobic conditions without the need for an anaerobic environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1a , b are scanning electron microscope images of the materials before and after modification; Figure 1c Transmission electron microscope coupled X-ray energy chromatography of nitrogen and phosphorus co-doped zero-valent iron composite material;
[0027] Figure 2a , b is the X-ray crystal diffraction pattern and magnified image of nitrogen and phosphorus co-doped zero-valent iron composite material;
[0028] Figure 3a , b are Raman spectra and FTIR spectra of nitrogen and phosphorus co-doped zero-valent iron composite materials;
[0029] Figure 4This is a comparison chart of the Tafel curves of the materials before and after modification;
[0030] Figure 5a , b are HRTEM and inverse fast Fourier transform images of the material before and after modification;
[0031] Figure 6 The scanning electron microscope coupled X-ray energy chromatogram of the nitrogen and phosphorus co-doped zero-valent iron composite material after the reaction;
[0032] Figure 7 The comparison diagram of Cr 2p orbital spectra of XPS of materials before and after modification after reaction;
[0033] Figure 8a , b is the effect diagram and rate constant bar graph of different proportions of nitrogen and phosphorus co-doped zero-valent iron composite materials in treating hexavalent chromium in polluted water;
[0034] Figure 9a , b is a comparison chart of the removal of hexavalent chromium by nitrogen-phosphorus co-doped zero-valent iron composite material and two phosphate-modified micron zero-valent irons without nitrogen source and a bar chart of rate constants;
[0035] Fig.10 This is a diagram showing the effect of using zero-valent iron composite materials co-doped with nitrogen and phosphorus at different concentrations to treat hexavalent chromium in polluted water.
[0036] Fig.11 This is a diagram showing the removal effect of different concentrations of hexavalent chromium by nitrogen and phosphorus co-doped zero-valent iron composite materials;
[0037] Fig.12a a, b, c, d are the removal effects of hexavalent chromium when the molar ratio of reduced iron powder to diammonium hydrogen phosphate is 1:0.035 and the pH of the chromium ion solution is 3, 5, 7, and 9, respectively;
[0038] Fig.13 This is a comparison chart of the Cr(VI) removal performance of the material before and after modification under anaerobic and aerobic conditions;
[0039] Fig.14 This is a graph showing the cyclic performance of nitrogen-phosphorus co-doped zero-valent iron composite material in reducing hexavalent chromium;
[0040] Figure 15 shows the removal effect of nitrogen and phosphorus co-doped zero-valent iron composite materials on four common heavy metals (Ni, Pb, Cd and Cu). DETAILED DESCRIPTION
[0041] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0042] The nitrogen-phosphorus co-doped zero-valent iron composite material synthesized by the method of the present invention can achieve rapid removal of hexavalent chromium under the coupling effect of adsorption and reduction. Adsorption is a prerequisite for the subsequent reduction of hexavalent chromium. The incorporated phosphorus is bound to the surface of zero-valent iron in the form of phosphate, which can reduce the binding energy of hexavalent chromium to the iron shell layer, thereby achieving an improvement in the adsorption effect. At the same time, diammonium hydrogen phosphate decomposes to generate ammonia under high-energy ball milling conditions of 800r / min. Nitrogen-containing gas molecules can act on the inside of the zero-valent iron lattice in the form of lattice nitrogen, stretching the Fe-Fe bond, weakening the interaction of the Fe-Fe bond, and accelerating the transfer of electrons from the iron core to the iron shell, thereby achieving complete reduction of the hexavalent chromium adsorbed to the surface in the previous stage.
[0043] Example 1
[0044] 0.094g, 0.236g, 0.33g, 0.471g and 0.66g diammonium hydrogen phosphate (the molar ratio of reduced iron powder to diammonium hydrogen phosphate is 0:0.01, 0:0.025, 0:0.035, 0:0.05 and 0:0.07) and 4g micron zero-valent iron were respectively put into a 100mL zirconium dioxide can and a certain amount of zirconium oxide beads were added. The mixture was ground at 800r / min for 40 cycles, each cycle for 30min, and each cycle was paused for 30s. Then the obtained powder was washed with oxygen-free water and dried under vacuum freezing conditions to synthesize nitrogen-phosphorus co-doped zero-valent iron composite NP-ZVI with different modification ratios. Unmodified ball-milled zero-valent iron, NaP-ZVI and KP-ZVI were prepared under the same ball milling conditions.
[0045] like Figure 1a As shown in Figure 1b, compared with the unmodified ball-milled zero-valent iron, the particle size of the modified material was significantly reduced, the surface roughness was significantly increased, and the surface was filled with fine crystal particles, which indicates that diammonium hydrogen phosphate reacted with zero-valent iron under high-energy ball milling conditions, destroying the passivated oxide shell on its surface, which is conducive to the refinement of zero-valent iron. Figure 1c The results of transmission electron microscopy (TEM) coupled with X-ray energy chromatography showed that the N and P elements were evenly distributed in the modified adsorption-reduction coupled micron zero-valent iron (NP-ZVI).
[0046] like Figure 2a As shown, the XRD test results show that the characteristic peaks of the diffraction patterns of the zero-valent iron composites co-doped with nitrogen and phosphorus in different proportions are consistent with the peaks of the standard diffraction patterns of zero-valent iron, indicating that the core crystal structure of the zero-valent iron composites co-doped with nitrogen and phosphorus has not changed. In addition, the research results confirm that the incorporation of nitrogen or phosphorus retains the crystal structure and effectively changes the surface properties of ZVI. After mechanochemical treatment, the grain size increases and the half-peak width becomes wider. Figure 2bAs shown in Figure 5, after mechanochemical treatment, the α-Fe(110) diffraction peak has a significant negative shift, indicating that there is a large amount of lattice expansion in NP-ZVI. This structural change may be the result of nitrogen interstitial doping.
[0047] like Figure 3a As shown in the figure, the Raman spectroscopy test results show that the peak characteristics of NP-ZVI are significantly changed compared with the unmodified micron zero-valent iron (M-ZVI), with a peak at 218.61 cm -1 and 285.6cm -1 Fe-N bonds were detected at NP-ZVI, which provides potential evidence for the formation of Fe-N species in NP-ZVI. Figure 3b As shown in Figure 2, FTIR analysis detected NP-ZVI (0.035) and NP-ZVI (0.05) at 540-600 cm -1 In addition, the spectrum of NP-ZVI showed significant changes, including peaks at 890, 1071, and 1233 cm -1 The new bands at 100 and 150 are related to the PO, Fe-OP and P=O stretching bonds, respectively. The test results show that both phosphorus and nitrogen form effective interactions with zero-valent iron.
[0048] like Figure 4 As shown, the Tafel curve results show that the corrosion potential of NP-ZVI increases from 0.56 V to 0.67 V compared with M-ZVI, indicating that the corrosion kinetics and electron release ability of NP-ZVI are significantly improved.
[0049] like Figure 5a As shown in Fig. 2 and Fig. 3, the measured results of adjacent lattice fringes of M-mZVI and NP-ZVI on the (1 1 0) crystal plane are 2.02nm and 2.05nm, respectively. This directly indicates that there is a tensile strain of about 1.49% in the modified NP-ZVI, confirming that nitrogen atoms can act on the internal lattice structure of Fe.
[0050] like Figure 6 As shown, a large number of Cr atoms are adsorbed on the surface of NP-ZVI after the reaction, which indicates that the nitrogen-phosphorus co-doped zero-valent iron composite material has a strong adsorption capacity for hexavalent chromium.
[0051] like Figure 7 As shown in the figure, the reduction efficiency of NP-ZVI for hexavalent chromium is 100% after the reaction, which is much higher than that of m-mZVI (56.8%). This result strongly proves that the nitrogen-phosphorus co-doped zero-valent iron composite material has a strong reduction ability on the basis of its extraordinary adsorption capacity.
[0052] Example 2 Effect of different ratios of nitrogen and phosphorus co-doped zero-valent iron composite materials on the removal of hexavalent chromium
[0053] Take 50mL of 5mg / L hexavalent chromium aqueous solution as simulated wastewater, add 0.1g of NP-ZVI (0-0.07) with different modified ratios, adjust the solution pH to 5, put it into a shaking table with a constant temperature of 25℃ and a speed of 150rpm / min, take samples regularly, and measure the hexavalent chromium concentration by spectrophotometry. At the same time, use unmodified ball-milled zero-valent iron as a control test. Figure 8a As shown in the figure, within 90 minutes of reaction, M-mZVI only removed 10.2% of hexavalent chromium, indicating that the unmodified material has poor adsorption and reduction ability for hexavalent chromium, and M-mZVI has a slow electron release ability on the iron core. After N and P were doped into mZVI, the removal efficiency of Cr(VI) gradually increased, and the modified NP-mZVI (0.035) could achieve complete removal of Cr(VI) under the same conditions. Figure 8b As shown in the figure, the removal of Cr(VI) by NP-ZVI (0-0.07) is not positively correlated with the dosage of (NH4)2HPO4. Instead, it follows a "bell-shaped" distribution, and NP-ZVI-0.035 (hereinafter referred to as NP-ZVI) shows the best performance in removing Cr(VI). The k value of NP-ZVI (0.035) is 0.056min -1 , about M-mZVI (0.0011min -1 ) is 51 times.
[0054] Example 3 Comparison of the effect of nitrogen-phosphorus co-doped zero-valent iron composite material and two phosphate micronized zero-valent irons without nitrogen source on the removal of hexavalent chromium
[0055] Take 50mL of 5mg / L hexavalent chromium aqueous solution as simulated wastewater, add 0.1g NP-ZVI, NaP-ZVI and KP-ZVI respectively, adjust the solution pH to 5, put it into a shaking table with a constant temperature of 25℃ and a speed of 150rpm / min, take samples regularly, and measure the hexavalent chromium concentration by spectrophotometry. Figure 9a As shown in Figure 2, within 90 minutes, the removal efficiency of Cr(VI) by NaP-ZVI and KP-ZVI was significantly lower than that by NP-ZVI. Figure 9b As shown in the figure, the reaction rate constants (k values) of NaP-ZVI and KP-ZVI are 0.0249min-1 and 0.0252min-1, respectively, which are less than half of the reaction rate value of NP-ZVI. The experimental results emphasize the key role of lattice nitrogen in improving the removal of hexavalent chromium by phosphate-modified zero-valent iron.
[0056] Example 4 Effect of different concentrations of nitrogen and phosphorus co-doped zero-valent iron composite materials on treating hexavalent chromium in polluted water
[0057] Take 50mL of 5mg / L hexavalent chromium aqueous solution as simulated wastewater, add 0.025g-0.15g of NP-ZVI, adjust the solution pH to 5, put it into a shaking table at a constant temperature of 25℃ and a speed of 150rpm / min, take samples at regular intervals, and measure the hexavalent chromium concentration by spectrophotometry. Fig.10 As shown in the figure, when the dosage increased from 0.05g / L to 1g / L and 2g / L, the removal rate of Cr(VI) was significantly improved, from 61.5% to 89.1% and 100%, respectively. This improvement may be due to the simultaneous improvement of the adsorption and reduction capabilities of the modified material. At the same time, when the dosage was 2g / L and 3g / L, NP-ZVI could completely remove Cr(VI) within 75min. Taking all factors into consideration, 2g / L was selected as the appropriate dosage of NP-ZVI for removing heavy metals.
[0058] Example 5 Removal effect of nitrogen and phosphorus co-doped zero-valent iron composite material on different concentrations of Cr(VI)
[0059] 0.1g NP-ZVI was put into 50mL hexavalent chromium aqueous solution with concentrations of 2mg / L, 5mg / L, 10mg / L and 15mg / L, respectively. The solution pH was adjusted to 5, and placed in a shaking table at a constant temperature of 25℃ and a speed of 150rpm / min. Samples were taken at regular intervals, and the hexavalent chromium concentration was measured by spectrophotometry. Fig.11 As shown in the figure, with the increase of initial Cr(VI) concentration, the removal efficiency of NP-ZVI decreased from 100% to 73.4% and then to 55.4%. The results show that with the increase of initial Cr(VI) concentration, the removal efficiency of NP-ZVI for hexavalent chromium gradually decreased.
[0060] Example 6 Comparison of the effect of different pH on the removal of hexavalent chromium from materials before and after modification
[0061] 50 mL of 5 mg / L hexavalent chromium aqueous solution was used as simulated wastewater, 0.1 g of NP-ZVI was added, and the solution pH was adjusted to 3, 5, 7, and 9, respectively. The solution was placed in a shaker at a constant temperature of 25°C and a speed of 150 rpm / min. Samples were taken at regular intervals, and the hexavalent chromium concentration was measured by spectrophotometry. Unmodified zero-valent iron was used as a control test. Fig.12a As shown in the figure, under the condition of pH = 3, the removal rate of Cr(VI) by unmodified ball-milled zero-valent iron within 90 minutes was only 19.6%, while the removal rate of Cr(VI) by nitrogen-phosphorus co-doped micronized zero-valent iron within 15 minutes was 92.2%, and Cr(VI) could be completely removed within 60 minutes. Figure 12b As shown in the figure, the removal rate of Cr(VI) by unmodified ball-milled zero-valent iron is only 14.4%, while the removal rate of Cr(VI) by nitrogen-phosphorus co-doped micronized zero-valent iron is 81% within 30 minutes, and Cr(VI) can be completely removed within 75 minutes. Fig.12cAs shown in Figure 2, compared with the unmodified ball-milled zero-valent iron, the Cr(VI) removal rate of the modified material increased from 6.5% to 68.1%. Fig.12d As shown, compared with the unmodified ball-milled zero-valent iron, the Cr(VI) removal rate of the modified material increased from 4.9% to 57.8%.
[0062] Example 7 Comparison of the effect of removing hexavalent chromium from the material before and after modification under anaerobic conditions and aerobic conditions
[0063] 0.1g NP-ZVI was put into 50mL of 5mg / L hexavalent chromium aqueous solution, and the anaerobic and aerobic conditions were set respectively. The pH of the solution was adjusted to 5, and the solution was placed in a shaking table at a constant temperature of 25℃ and a speed of 150rpm / min. Samples were taken at regular intervals, and the hexavalent chromium concentration was measured by spectrophotometry. Unmodified zero-valent iron was used as a control test. Fig.13 As shown, the removal performance of NP-ZVI for Cr(VI) under anaerobic conditions is slightly higher than that under aerobic conditions, indicating that the competitive side reaction of oxygen reduction reaction (ORR) has negligible effect on the system, indicating that NP-ZVI does not need to maintain an anaerobic environment for the degradation of hexavalent chromium and has good air adaptability.
[0064] Example 8 Cyclic Effect of Nitrogen-Phosphorus Co-doped Zero-Valent Iron Composite Material on Removal of Hexavalent Chromium
[0065] Take 50mL of 5mg / L hexavalent chromium aqueous solution as simulated wastewater, add 0.1g of nitrogen and phosphorus co-doped micron zero-valent iron, adjust the solution pH to 5, put it into a shaking table at a constant temperature of 25℃ and a rotation speed of 150rpm / min, take samples regularly, and measure the hexavalent chromium concentration by spectrophotometry. When all the hexavalent chromium in the system is removed, use a magnet to absorb and recover the added zero-valent iron, wash and dry it with deionized water, and then put it into 50mL of 5mg / L hexavalent chromium aqueous solution to continue to measure the removal of hexavalent chromium. The above steps are completed once and counted as one cycle. Fig.14 As shown in Figure 2, NP-ZVI still maintained over 80% Cr(VI) removal efficiency after five consecutive cycles of testing. This result highlights the extraordinary durability and reusability of NP-ZVI in repeated applications.
[0066] Experimental Example 9 Removal effect of NP-ZVI on four common heavy metals (Ni, Pb, Cd and Cu)
[0067] 50mL of 10mg / L Cu 2+ , 5mg / L Ni 2+ , 5mg / L Pb 2+ and 2 mg / L Cd 2+The aqueous solution is simulated wastewater, to which 0.1 g of NP-ZVI is added, the pH of the solution is adjusted to 5, and the solution is placed in a shaker at a constant temperature of 25°C and a rotation speed of 150 rpm / min. Samples are taken at regular intervals, and the concentration of heavy metals in the solution is measured using an inductively coupled plasma mass spectrometer (ICP-MS). Fig.15a As shown in a, b, c, and d, the removal rates of four common heavy metals (Ni, Pb, Cd, and Cu) by NP-ZVI were close to 100% within 120 min, indicating that NP-ZVI has strong applicability for heavy metal pollution remediation applications.
Claims
1. A method for preparing a nitrogen-phosphorus co-doped zero-valent iron composite material, characterized in that: Using reduced iron powder and diammonium hydrogen phosphate as raw materials, phosphorus and nitrogen are doped on the surface and inside of zero-valent iron through solid phase ball milling to obtain a nitrogen-phosphorus co-doped zero-valent iron composite material.
2. The method for preparing the nitrogen-phosphorus co-doped zero-valent iron composite material according to claim 1, characterized in that: The preparation process of the solid phase ball mill is specifically as follows: placing reduced iron powder and diammonium hydrogen phosphate in a ball mill equipped with grinding media for high-energy ball milling; the grinding media is one or more of agate beads, iron beads, steel balls and zirconium oxide beads, with a diameter of 1-20 mm.
3. The method for preparing the nitrogen-phosphorus co-doped zero-valent iron composite material according to claim 2, characterized in that: During the solid phase ball milling process, the molar ratio of reduced iron powder to diammonium hydrogen phosphate is 1:0.01-0.
07.
4. The method for preparing the nitrogen-phosphorus co-doped zero-valent iron composite material according to claim 2, characterized in that: The ball mill grinds 40 times at 800 r / min, each time for 30 minutes, and pauses for 30 seconds after each time. The total grinding time is 20 hours.
5. The method for preparing the nitrogen-phosphorus co-doped zero-valent iron composite material according to claim 4, characterized in that: The ball milling equipment is a planetary ball mill, a vibrating ball mill or a sand mill.
6. A nitrogen-phosphorus co-doped zero-valent iron composite material, characterized in that: A nitrogen and phosphorus co-doped zero-valent iron composite material obtained by the preparation method described in any one of claims 1 to 5.
7. Use of the nitrogen and phosphorus co-doped zero-valent iron composite material according to claim 6 in wastewater treatment and / or groundwater pollution remediation, characterized in that: The nitrogen and phosphorus co-doped zero-valent iron composite material was added to the hexavalent chromium aqueous solution to be treated, and after adjusting the pH, it was placed in a shaking table with a constant temperature of 25° C. and a rotation speed of 150 rpm / min. Samples were taken at regular intervals, and the hexavalent chromium concentration was measured by spectrophotometry.
8. The use according to claim 7, characterized in that: The addition concentration of the nitrogen and phosphorus co-doped zero-valent iron composite material is 0.5 g / L-3 g / L.
9. The use according to claim 7, characterized in that: The hexavalent chromium aqueous solution is simulated wastewater, and the concentration of hexavalent chromium in the simulated wastewater is 2-15 mg / L.
10. The use according to claim 7, characterized in that: The pH of the hexavalent chromium aqueous solution to be treated is adjusted to 3-9.
Citation Information
Patent Citations
Preparation method and application of nitrogen-doped zero-valent iron composite material
CN111847541A
Transition metal phosphide modified nano-iron composite material, preparation method and application thereof
CN113649034A
Iron phosphorus composite material capable of slowly releasing ferrous iron as well as preparation method and application of iron phosphorus composite material
CN115739927A
Phosphorus-doped zero-valent iron modified material, preparation method thereof and method for efficiently reducing and removing pollutants by using phosphorus-doped zero-valent iron modified material
CN115784412A